Survey of Several Words about Religion and Prejudice (According to the Syunik-Artsakh dialect dictionary) - Kumunts, Mher (Bulletin of Yerevan University B: Philology, 2022)
In the dialectical vocabulary of Syunik-Artsakh, religious words make up 58% com-pared to Armenian, and compared to the list of K. Baq compiled by Baku - 66%. Three words have been added to the thematic group formed by the previous ones, according to the data of Syunik-Artsakh dialectical vocabulary, which, we think, are of In-do-European origin: kashk-kasq (քաշկ – քաշկ/ք), sundu-sundu (kuku) (սո̈ւնդո̈ւ-սունդու(կուկու)), kupel-kup(el) (կուփել-կո̈ւփ(էլ)). There’s a question of whether kaj (քաջ) և kajq (kashk) քաջք (քաշկը)is the general basis of the words. It is more probable that kash-q / k (քաշք/կ), " evil spirit", has Indo-European origin: *u̯ek-ti- "something, thing, man, being". The word (Սունդու) probably derives from the root *sent – “direct, go, motion, way, road:” sundukuku (սունդուկուկու), Sindara (Սինդարա). We think that the word kup(el) (կո̈ւփ(էլ)): 1. “Touch, blow, blow of a person, child, evil spirit, demon or angel” in the vocabulary of the Syunik-Artsakh dialect in meaning and form it is related to primary and secondary forms of the Indo-European root *(s)kep(h)- || *(s)kō̆p-: 1. "cover, cover, cover, protect"; 2. "beat, cut" (possible development from the last meaning). In the Pokorny dictionary, under the word (s)kō̆p-, a number of words are mentioned that reflect the semantic similarity of the word "kup(el)-" (կո̈ւփ(էլ)) in Indo-European languages, for example, Old High German scaffōn "form, cause", Old Norse skap "form, mental condition", etc.